Tailoring Al-Doped ZnO Nanoparticles via Scalable High-Energy Ball Milling–Solid-State Reaction: Structural, Optical, and Dielectric Insights for Light-Activated Antimicrobial Defense Against Medical Device Pathogens - Zurayfah Al-Shammari; Imen Massoudi; Amani Rached; Ibtisam Ababutain; Azzah Alghamdi; Reem Aldakheel; Kamal Amin; Essam Kotb; Amor Ben Ali (Crystals)
This study reports the synthesis of aluminum-doped ZnO nanoparticles (Al-ZnO NPs) via a top-down mechanochemical solid-state reaction (SSR) approach using high-energy ball milling (HEBM) as a rapid, controllable, and efficient method. Al-ZnO samples were characterized using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), and UV-Vis diffuse reflectance spectroscopy. Significantly, the band gap decreased by 0.215 eV when transitioning from pure ZnO to 9 wt.% Al-doped ZnO (Al-ZnO9). TEM analysis showed that after 4 h of milling at 1000 rpm, the particle size was reduced to 59 nm, exhibiting a spherical morphology crucial for enhanced bioactivity. The antimicrobial properties of the Al-ZnO NPs were evaluated using the well diffusion method against various pathogenic microorganisms, with a particular focus on Staph. aureus ATCC 29213 and Staph. epidermidis ATCC 12228, given their clinical significance as common pathogens in infections related to medical implants and prosthetics. Al-ZnO9 demonstrated superior antibacterial performance, producing inhibition zones of 13 mm and 15 mm against Staph. aureus and Staph. epidermidis, respectively. Moreover, exposure to visible light further amplified the antimicrobial activity. This research underscores the potential for the scalable production of Al-ZnO NPs, presenting a promising solution for addressing infections linked to implanted medical devices.